Confirmation of European snow vole Chionomys nivalis (Mammalia: Rodentia: Cricetidae) occurrence in Portugal. Issue 1 (2nd January 2016) - Barros, P.; Vale-Gonçalves, H. M.; Paupério, J.; Cabral, J. A.; Rosa, G.
Abstract: The European snow vole ( Chionomys nivalis ) is a microtine rodent with a highly fragmented distribution range, mostly associated with the main mountain systems from southern Europe to Turkmenistan. In this paper we confirm the occurrence of the snow vole in Portugal, based on morphological characteristics, biometrics and genetic analysis of two individuals captured in the Montesinho Mountain range (northeastern Portugal). Both mitochondrial and nuclear genetic markers were used to confirm the species identity. The analysis of cytochrome b supports previous conclusions on the phylogeographic structure of the species, revealing the existence of several distinct lineages. Moreover, it shows that the Portuguese specimens are closely related to the other Iberian populations. This finding is of great interest as it adds new information regarding the spatial distribution of the snow vole, by redefining the southwestern limits of the species' range, and it highlights the need for accurate assessment of regional small mammal population trends and conservation status.